Synthesis, Characterization and Antioxidant Activity of Some New Schiff base Derived from Cytosine - Ali A. Mahmood (Journal of Global Pharma Technology, 2016)
Cytosine is used to synthesize several derivatives of Schiff base when reacted with some aldehydes which are refluxed by using ethanol as a solvent and non solvent with adomestic microwave (Compounds A1-A4). These products of the Schiff base are treated first with chloroacetyl chloride to synthesize four-membered heterocycles (Compounds B1-B4). After that, they treated with hydroxyl acetic acid to synthesize five-membered heterocyclic (Compounds C1-C4). In the third step, the products are used to react with amaleic acid anhydride to produce seven-membered heterocyclic (Compound D1-D4). The antioxidant activity of the compounds (A1-A4) and two of the compounds (B1, B3), (C1, C3) and (D1, D3) in different concentrations of (100, 200, 300, 400 and 500 mg/ml) are tested with 1, 2-Di Phenyl-2-Picryl Hydrazyl (DPPH) for scavenging a radical activity. Finally, these compounds are diagnosed by several technical devices such as IR, proton1HN.M.R and13C N.M.R. spectroscopy.Keywords: Synthesis; Cytosine; Schiff Base;